Chronic Heart Failure in Rheumatoid Arthritis Patients (Part II): Difficulties of Diagnosis - D. S. Novikova; H. V. Udachkina; I. G. Kirillova; T. V. Popkova (Рациональная фармакотерапия в кардиологии)
Rheumatoid arthritis (RA) is characterized by a twofold increase in morbidity and mortality due to chronic heart failure (CHF). At the same time, the prevalence of CHF among RA patients is significantly underestimated. The aim of the review was to analyze the results of the main studies on the features of the clinical presentation of heart failure (HF) in RA patients, the role of visualization techniques and biomarkers in the diagnosis of HF and preclinical dysfunction of the myocardium. HF in patients with RA is characterized by a predominance of HF with a preserved left ventricular ejection fraction (LVEF). The use of clinical diagnostic criteria in RA patients can lead to both over- or underdiagnosis of CHF. Systolic dysfunction estimated by LVEF is rare in RA and does not reflect the real frequency of myocardial dysfunction. Echocardiography (ECHO-CG) with tissue Doppler echocardiography (TDE) and visualization of myocardial deformation, magnetic resonance imaging (MRI) of the heart in RA patients revealed a high frequency of HF with preserved ejection fraction, left ventricular remodeling and hypertrophy, pre-clinical systolic and diastolic dysfunction. Determination of natriuretic peptides is useful for verifying the diagnosis of HF and estimating the prognosis in this cohort, despite the possible decrease in the sensitivity and specificity of these indicators in RA patients. The review discusses the advantages of MRI of the heart, including quantitative T1 and T2 regimens, in the diagnosis of myocarditis, myocardial fibrosis, and myocardial perfusion disorders in RA patients. In order to verify the diagnosis of heart failure and detect pre-clinical myocardial dysfunction in RA patients, the determination of natriuretic peptides concentration should become part of the routine examination, beginning with the debut of the disease, along with the collection of a cardiological history, physical examination, ECHO-CT with TDE, and visualization of myocardial deformation. Evaluation of the quantitative characteristics of tissue according to MRI of the heart could improve the diagnosis of myocardial damage.